Habitat mapping and possibilities for evaluation on environmental management of Vésztő-Mágor Nature Reserve - Nagy, Anita; Kiss, Tímea; Saláta, Dénes; Süli, Ágnes; Szalkay, Csilla; S.-Falusi, Eszter; Penksza, Károly; Pápay, Gergely (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2019)
Habitat mapping was carried out on Vésztő-Mágorpuszta Nature Reserve based on the Hungarian National Habitat Classification System. Habitat codes occurring within habitat patches and short description of each patch are given in parallel with a detailed species list (completed with dominance relations). Based on these, a habitat map of the area and habitat-based thematic maps of sodic areas influenced by water were prepared. The central part of the observed area is diverse and valuable from a botanical point of view, part of the area with complex patches is sodic, in between with sporadic lowland swards and some smaller lowland steppes. Possible reason for abandonment of management on these areas could be the influence of water. Rate of areas with higher dominance of weeds is small.